2009
DOI: 10.1007/s11071-009-9619-4
|View full text |Cite
|
Sign up to set email alerts
|

Hopf bifurcation and intermittent transition to hyperchaos in a novel strong four-dimensional hyperchaotic system

Abstract: This paper presents a new four-dimensional autonomous system having complex hyperchaotic dynamics. Basic properties of this new system are analyzed, and the complex dynamical behaviors are investigated by dynamical analysis approaches, such as time series, Lyapunov exponents' spectra, bifurcation diagram, phase portraits. Moreover, when this new system is hyperchaotic, its two positive Lyapunov exponents are much larger than those of hyperchaotic systems reported before, which implies the new system has strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…A dynamic model of finance has been reported in [29][30][31], which is composed of four subblocks, production, money, stock, and labor force, and expressed by four first-order differential equations. The model describes the time variations of four state variables: the interest rate , the investment demand , the price exponent , and the average profit margin .…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A dynamic model of finance has been reported in [29][30][31], which is composed of four subblocks, production, money, stock, and labor force, and expressed by four first-order differential equations. The model describes the time variations of four state variables: the interest rate , the investment demand , the price exponent , and the average profit margin .…”
Section: Model Formulationmentioning
confidence: 99%
“…Since this chaotic finance system is proposed, many works have been done for this finance system [29,30]. Recently, a novel hyperchaotic finance system [31] is presented in 2010 and some important results have been obtained. However, there are some limitations in the existing results.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, much eff ort has been devoted to the theory of chaos control, primarily in the areas of unstable equilibrium points and unstable periodic solutions (Hubler, 1989). The methods which have been developed are in particular suitable for the case of chaos suppression in various chaotic systems (Wu, 2010;He, 2013;Chen, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chaos in this system is not very obvious, and the largest Lyapunov exponent is 0.034432. It is found that the largest Lyapunov exponent presented in [15] is 29.79, but it is a strong four-dimensional hyperchaotic system which is not concerned with economy. …”
Section: Lyapunov Exponents and Lyapunov Dimensionmentioning
confidence: 99%